The Role of Socio-psychological Training in the Development of Communication Skills of Customs Officers - Nizomovich, Aslonov Ilkhom (International Journal of Psychosocial Rehabilitation, 2020)
The acquisition of communication skills and abilities is one of the factors ensuring the effectiveness of a particular activity. Communicative skills play an important role in preventing emotional barriers and stresses arising in professional activities. The article scientifically analyzes the psychological nature of professional communication between customs officers and the psychological factors that influence it. The importance of socio- psychological training in achieving the effectiveness of professional communication in the activities of customs officers and the acquisition of communication skills is disclosed.